Effects of supplemental protein and energy on digestion and urea kinetics in beef cattle - E.A. Bailey; D.W. Brake; David E. Anderson; M.L. Jones; Evan C. Titgemeyer; K. C. Olson (Kansas Agricultural Experiment Station Research Reports, 2010)
Previous research at Kansas State University has shown that providing supplemental energy when protein is deficient will cause a decrease in digestion of low-quality forage. Our project examined the effects of supplemental glucose on low-quality forage intake and digestion. Urea recycling is a mechanism by which cattle preserve nitrogen when faced with a deficiency. Young, growing cattle receiving sufficient protein recycle large amounts of nitrogen to the rumen. Our goal was to explore the effects of providing supplemental energy and protein to cattle that are on the downward side of their growth curve. Specifically, we measured intake, digestion, and urea kinetics in these animals.
Keywords: Cattlemen' s Day; 2010; Kansas Agricultural Experiment Station contribution; no. 10-170-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1029; Beef Cattle Research; 2010 is known as Cattlemen' s Day; Beef; Energy; Urea; Protein